A New Species of The Spider Genus Xysticus (Araneae: Thomisidae) From Arizona - J. H. Redner; C. D. Dondale (Psyche: A Journal of Entomology)
The North American crab spiders are now comparatively well known taxonomically. This is particularly true of the species in the large genus Xysticus, which has been twice revised continentally by Gertsch (1939, 1953) and treated in more regional works by Buckle and Redner (1964), Schick (1965), and Turnbull, et al. (1965). It seems probable that any additional new forms that will be discovered will be from remote parts of the continent or in sibling relationship with known species. Several species have, however, been described only from one sex.